THE STRUCTURAL AND SEMANTIC PROPERTIES OF COMPOUND NOUNS WITH SOMATIC COMPONENTS IN THE GERMAN LANGUAGE - Lysak, M. (Linguistic and Conceptual Worldviews, 2019)
This article is devoted to the structural and semantic properties of somatic compound nouns in the German language. It discusses the theoretical premises of the study of compound nouns, determines the basic characteristics and types of such compounds, and considers the metaphorical rethinking of compounds, to which the personification of inanimate nature is attributed, that represent another typical manifestation of the anthropomorphic metaphor and aт egocentric model of spatial orientation.
Keywords: compound nouns, structural and semantic properties, somatic component, word formation, A and B constituents, metaphor, metonymy